Optimization of the Formulation of Rice Biscuits Supplemented with D. Edulis (L.) Powder Using Response Surface Methodology - Eliane Flore Eyenga; Hippolyte Tene Mouafo; Mercy Bih Loh Achu; Wilfred F. Mbacham; Sali Atanga Ndindeng (International Journal of Food Science)
Trends in the food industry are nowadays directed towards the reduction of the level of trans fatty acids in food intended for human consumption. The present study was designed and aimed at valorizing Dacryodes edulis (L.) powder as a substitute for margarine in the production of functional rice biscuits. The effect of substituting margarine and refined wheat flour with D. edulis powder locally called safou and rice flour, respectively, at different proportions was assessed for the sensory and physicochemical properties of the formulated biscuits. For this, statistical models were developed, validated, and optimized using the response surface methodology with the Doehlert design as a tool. The results showed that an increase in the substitution rate of margarine with of D. edulis powder enhanced the aroma while the substitution of refined wheat flour with rice flour led to an improvement of the overall quality of the biscuits. The optimal composition of dough for the production of biscuits with satisfying sensory properties was 20.24% of wheat flour, 24.51% of rice flour, 19.09% of margarine, and 2.47% of D. edulis powder. The optimized biscuit which scored the highest overall acceptability contained proteins (10.33 g/100 g DM), fat (27.66 g/100 g DM), crude fibers (2.5 g/100 g DM), ash (3.55 g/100 g DM), and carbohydrates (54.01 g/100 g DM). It has an energy density of 506.3±0.1 kcal/g and could therefore be suitable for the management of malnutrition. Mineral analysis revealed that the biscuit contained sodium (0.200 mg/100 g), potassium (0.192 mg/100 g), phosphorus (0.123 mg/100 g), iron (33.60 ppm), and zinc (26.81 ppm) at levels satisfying the recommended daily intakes. The results of this study demonstrated the suitability of safou as substitute of margarine in the rice biscuit formulation and suggests the potential of the formulated biscuits in the management of malnutrition and noncommunicable diseases such as hypertension, obesity, and cardiovascular diseases.